The Influence of Competence and Commitment of Village Government Apparatus on Community Income Through Bumdes Management Performance in Sinjai District - Yakub; Muhammad Azis; Siti Hasbiah (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research was carried out to determine the influence of the competence and commitment of village government officials on the performance of Bumdes management and the income of village communities in Sinjai Regency for 199 research respondents. This research is quantitative research that emphasizes analysis based on data and numbers and relies on the conclusion of the results on an error probability of rejecting the null hypothesis (Ho) which is built on a strong theory. Data was obtained through questionnaires and documentation with probabilistic sampling. Next, the data was analyzed descriptively and inferentially using structural equation modeling techniques to test the 8 hypotheses in this research. Data collection was carried out through documentation, interviews and questionnaires. Next, the research data was analyzed through Structural Equation Modeling (SEM), which is called structural equation modeling. SEM is a combination of three statistical concepts, namely the concept of factor analysis which is included in the measurement model, the concept of regression through a structural model, and the concept of path analysis. The results of the research show that 1) The competence of village government officials influences the income of village communities in Sinjai Regency. 2) The commitment of village government officials influences the income of village communities in Sinjai Regency. 3) The competence of village government officials influences the performance of Bumdes management in Sinjai Regency. 4 ) The commitment of village government officials influences the performance of Bumdes management in Sinjai Regency. 5) The competence of village government officials influences village community income through the performance of Bumdes management in Sinjai Regency. 6) The commitment of village government officials influences the income of village communities through the performance of bundes management in Sinjai Regency and 7) The performance of bundes management has no effect on the income of village communities in Sinjai Regency.